2014
DOI: 10.4236/fns.2014.522238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Quality of One Layer Flat Bread Supplemented with Beans and Sorghum Baked on Hot Metal Surface

Abstract: The present study was carried out to develop the wheat flour nutritional value with good quality of unleavened bread by adding 5%, 10% and 15% of bean or sorghum flour. Water absorption was increased by addition of bean flour as a result of increase rate of substitution. Dough stability decreased for bean and sorghum blends as the same as increasing addition. Softening gradually increased with increasing the addition of beans or sorghum. Addition of 15% sorghum had the highest degree of softening compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 28 publications
8
16
2
Order By: Relevance
“…Control bread had the highest content of carbohydrate (38.65%), while the bread enhanced with 15% SLSF had the lowest carbohydrate content (34.72%). These results are closed to those found by Seleem and Omran (2014), who reported that addition of beans caused an increased in ash and fiber contents of prepared bread.…”
Section: Proximate Chemical Compositioncontrasting
confidence: 89%
“…Control bread had the highest content of carbohydrate (38.65%), while the bread enhanced with 15% SLSF had the lowest carbohydrate content (34.72%). These results are closed to those found by Seleem and Omran (2014), who reported that addition of beans caused an increased in ash and fiber contents of prepared bread.…”
Section: Proximate Chemical Compositioncontrasting
confidence: 89%
“…This may imply that products that are made with partial substitution of WBF in wheat may be nutritionally advantageous compared to those made with wheat flour alone. There were significant differences (p < 0.05) in the ash, crude fat and crude protein contents of WBF and those of 100-wheat.The higher contents of protein, ash, and fibre in the WBF than 100-wheat recorded in this study are supported by the reports of Ramezani et al (2013) and Seleem and Omran (2014) who noted similar results in flours of beans and wheat..…”
Section: Discussionsupporting
confidence: 91%
“…White beans (Phaseolus vulgaris) are legumes, which are regarded as "poor man's meat". They supply protein, complex carbohydrates, fiber and essential vitamins and minerals to the diet, which are low in fat and sodium and contain no cholesterol (Seleem and Omran, 2014). The inclusion of legume, especially beans to cereal based products could be a good option for increasing nutritional intake of people.…”
Section: Introductionmentioning
confidence: 99%
“…DRSF gradually increased fiber contents to be 2.93, 3.6 and 4.25% in 5, 10 and 15% added DRSF, respectively. These results are closed to that found by Seleem & Omran (2014) who stated that bread enhanced with beans had the highest values in protein, ash and fiber compared with wheat and sorghum bread. Antioxidant activity:…”
Section: Proximate Chemical Compositioncontrasting
confidence: 99%